High performance air electrode for solid oxide regenerative fuel cells fabricated by infiltration of nano-catalysts - Yoon, K.J.; Hong, J.; Kim, H.; Son, J.-W.; Lee, J.-H.; Kim, B.-K. (ECS Transactions, 2015)
A high performance air electrode was fabricated by infiltration of nano-catalysts into a porous backbone for high-temperature solid oxide regenerative fuel cells (SORFCs). The Sm0.5Sr0.5CoO3 (SSC) nano-catalysts were uniformly synthesized in a porous La0.6Sr0.4Co0.2Fe0.8O3 (LSCF) - gadolinia-doped ceria (GDC) composite backbone by impregnation of nitrate precursor solution followed by homogeneous nucleation induced by urea decomposition. Significant improvement in the electrochemical performance was achieved in both solid oxide fuel cell (SOFC) and solid oxide electrolysis cell (SOEC) modes. ？ The Electrochemical Society.